2014
DOI: 10.7182/pit2014830
|View full text |Cite
|
Sign up to set email alerts
|

Living Donor Transplant Education for African American Patients with End-Stage Renal Disease

Abstract: Living ACTS is effective at increasing and maintaining knowledge about LDKT among African American patients with end-stage renal disease who are considering transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 28 publications
0
72
0
Order By: Relevance
“…In a prior study focusing on disadvantaged populations to improve kidney transplant access, health educators were randomized to visit black patients with ESKD and guests in their homes, which resulted in a trend toward increased living donor transplant and increased knowledge and willingness to discuss transplantation (37). Arriola et al (38) also found that a culturally sensitive educational intervention at a transplant center increased knowledge and willingness to talk to patients' families about transplant; however, key steps, such as waitlisting and transplant, were not examined. There are several explanations for why we did not observe a difference in waitlisting among intervention (5) 9 (5) 10 (5) 0.89 Figure 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a prior study focusing on disadvantaged populations to improve kidney transplant access, health educators were randomized to visit black patients with ESKD and guests in their homes, which resulted in a trend toward increased living donor transplant and increased knowledge and willingness to discuss transplantation (37). Arriola et al (38) also found that a culturally sensitive educational intervention at a transplant center increased knowledge and willingness to talk to patients' families about transplant; however, key steps, such as waitlisting and transplant, were not examined. There are several explanations for why we did not observe a difference in waitlisting among intervention (5) 9 (5) 10 (5) 0.89 Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Larger, multicenter studies testing the effectiveness of a patient navigator may be warranted, particularly because the absolute effect of the navigator was small after the 500 days (15 versus five waitlisting events). Perhaps future studies should administer multiple interventions along with patient navigation, such as educational interventions that take place in either a patient's home (21) or the dialysis facility (39) and/ or culturally sensitive education within a transplant center focusing on living donor transplant (38), to potentially have a synergistic effect on waitlisting and help address the major barriers faced by this population. Larger studies with longer follow-up could also examine important outcomes beyond waitlisting, including receipt of a living or deceased donor transplant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some of these decision aids overlap across categories, we broadly classified the 12 decision aids across the following types: 1) comprehensive LDKT education, 2) culturally sensitive, targeted to specific audience, 3) recipient education, 4) potential donor recruitment and education, and 5) healthcare provider education. Four of these aids have completed evaluation and demonstrated effectiveness [4548]. Six are undergoing effectiveness testing [49–54] (Table 2).…”
Section: Introductionmentioning
confidence: 99%
“…Living About Choices in Transplantation and Sharing (Living ACTS) [45] is a decision aid developed using the IPDAS Guidelines and aimed at overcoming communication barriers related to LDKT that are culturally-sensitive to African Americans. Living ACTS was adapted from a community project with local churches aimed to improve the public commitment to deceased donation [61].…”
Section: Introductionmentioning
confidence: 99%